Pteridofitas de la Reserva “Valle del Arroyo Cuñá Pirú” (Misiones, Argentina) - Márquez, Gonzalo Javier (2006)
Nine families, 29 genera and 52 species and infraespecific taxa of Pteridophytes are reported for the nature reserve “Cuñá Pirú”. The most represented genus is Asplenium with eight species, two of them being new records for the Argentinean flora. Between one to three species were recorded for the remaining genera. These plants mainly grow deep into the forest, or along forest trails and stream banks. Keys to all groups and entities, literature, distribution and ecology references are included.